PENGARUH RASIO SOLVABILITAS, PROFITABILITAS, DAN LIKUIDITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2020 - Digdowiseiso, Kumba; Santika, Sindi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of the variables Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Quick Ratio on Profit Growth in Coal Mining Companies listed on the Indonesia Stock Exchange for the period 2013-2020. The population of this study are coal mining companies that have been and are still listed on the Indonesia Stock Exchange for the 2013-2020 period. Sampling technique using saturated sampling technique and obtained a sample of 17 companies. This study uses secondary data in the form of financial statements that meet the criteria, data obtained from financial statements obtained from the Indonesia Stock Exchange which can be accessed through www.idx.co.id. The analytical technique used in this study is linear regression of panel data using the STATA 16 program. The results show that the DER variable has a positive and insignificant effect on profit growth. The NPM variable has a negative and significant effect on profit growth. The QR variable has a negative and insignificant effect on profit growth.